Development of amorphous silicon solar cells with plasmonic light scattering. (May 2017) - Crudgington, L.J.; Rahman, T.; Boden, S.A.
Abstract: This paper reports the result of simulation and fabrication of the optical effects of metallic nano-particle arrays within amorphous silicon thin-films. A finite-difference time domain approach is used to design and model nano-particle arrays within opto-electronic models of thin-film amorphous silicon. An increase in optical scattering and localized surface plasmon resonance is observed, resulting in an increase in power absorption within the material active region and a reduction in optical reflection from the film surface. It is shown that this enhancement in optical performance depends on the particle size, shape, position within the structure and proximity to the metallic back reflector. Process development of metal-island films on silicon and glass, followed by the fabrication and measurement of amorphous silicon P-I-N devices featuring plasmonic nano-particles is demonstrated; showing an enhancement in-keeping with results achieved using simulation.